2021
DOI: 10.5435/jaaosglobal-d-20-00216
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Change in USMLE Step 1 Grading on Orthopaedic Surgery Applicants: A Survey of Orthopaedic Surgery Residency Program Directors

Abstract: Introduction: Recently, the Federation of State Medical Boards and the National Board of Medical Examiners, cosponsors of the United States Medical Licensing Examination (USMLE), changed the USMLE Step 1 results from a three-digit score to a pass/fail format. The purpose of this study was to analyze the opinions of program directors (PDs) to predict how the evaluation of orthopaedic surgery residency applicants will change following the change. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 13 publications
3
21
0
Order By: Relevance
“…Corresponding to the emphasis orthopaedic program directors place on scholarly activities, the mean number of publications and presentations of orthopaedic surgery residency applicants doubled between 2007 and 2014 [11], and this trend is likely to continue as the United States Medical Licensing Examination Step 1 converted to pass/fail scoring [15,29]. Because the timeline to publication of research projects may be lengthy, many projects may not be published before application deadlines.…”
Section: Introductionmentioning
confidence: 99%
“…Corresponding to the emphasis orthopaedic program directors place on scholarly activities, the mean number of publications and presentations of orthopaedic surgery residency applicants doubled between 2007 and 2014 [11], and this trend is likely to continue as the United States Medical Licensing Examination Step 1 converted to pass/fail scoring [15,29]. Because the timeline to publication of research projects may be lengthy, many projects may not be published before application deadlines.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent study by Bernstein et al found that over 48% of programs in the FREIDA database failed to include USMLE Step requirements, and of the 141 programs participating in the ORIN database, most did not report the USMLE Step median or cutoff score 28 . Aside from examination scores, other factors such as performance during away rotations, personal knowledge of the applicant, clerkship grades, letters of recommendation from orthopaedic surgeons, Alpha Omega Alpha status, and research experience will gain significance 26,27 . Mun et al found that 69.3% of orthopaedic surgery program directors surveyed are now advocating for a graded preclinical curriculum 26 .…”
Section: Discussionmentioning
confidence: 99%
“…As the number of applicants applying to orthopaedic surgery programs rises and the transition of USMLE Step 1 and COMLEX Level 1 to pass/fail, program directors may now place more emphasis on other factors, including USMLE Step 2 and COMLEX Level 2 scores 26,27 . However, a recent study by Bernstein et al found that over 48% of programs in the FREIDA database failed to include USMLE Step requirements, and of the 141 programs participating in the ORIN database, most did not report the USMLE Step median or cutoff score 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the interview process alone has cost applicants an average of $5,000 to 7,000 and even up to $20,000 14 , 21 . One area of concern some authors have suggested is that students may consider applying for more away rotations because of the transition to the pass/fail USMLE scoring 20 . Inevitably, this could further drive up the cost of the away rotations.…”
Section: Discussionmentioning
confidence: 99%